The role of time-monitoring behaviour in time-based prospective memory performance in younger and older adults. Issue 1 (2nd January 2020) - Mioni, Giovanna; Grondin, Simon; McLennan, Skye N.; Stablum, Franca
ABSTRACT: Time-based prospective memory (TB-PM) is the ability to remember to perform an action at a specific moment in the future. Accurate TB-PM performance requires several cognitive processes that are known to decline in normal ageing. This study aimed to examine associations between TB-PM performance and executive functions and time perception in younger and older adults. TB-PM was assessed with the Virtual Week paradigm. Using a within-subjects experimental manipulation, participants performed TB-PM tasks both when a clock was in constant view and when it was hidden behind a button. Results showed that younger adults performed significantly better than older adults on all TB-PM task types, and checked the clock more often, and more strategically. Clock availability improved TB-PM performance in all participants. Correlational analyses showed that TB-PM accuracy was positively related to clock-checking frequency but unrelated to time perception. Relationships between executive functions and TB-PM differed across age groups as well as TB-PM task types. The findings suggest that different cognitive processes are required for different types of TB-PM tasks and in different ages. These results highlight the importance of considering TB-PM task parameters when investigating the role of cognitive processes in PM performance and their contribution to age-related PM decline.